Design And Development of Data Input Application For Covid-19 Vaccination Recipients In Sukoharjo Regency Based on Website - Ihsan Cahyo Utomo; Umi Fadlilah; Ragiel Abiul Pratama; Aldin Nasrun Minalloh (Institut Teknologi Bisnis AAS Indonesia, 2023)
Corona Virus Deseas 19 (Covid-19) is an infectious disease caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This disease was first identified in December 2019 in Wuhan, the capital of China's Hubei province, and since then Covid-19 has spread widely throughout the world including regions in Indonesia. One of the efforts of the World Health Organization (WHO) to break the chain of transmission of Covid-19 is to implement health protocols and carry out the Covid-19 vaccine program. Indonesia is one of the countries implementing the Covid-19 vaccination program in order to break the chain of transmission of Covid-19. Based on data from the Ministry of Health of the Republic of Indonesia on November 23, 2021, a total of 135,716,042 vaccinations were recorded for dose 1 and 90,520,201 for dose 2, while the vaccination target was 208,265,720. Sukoharjo Regency is one of the districts with quite high cases, and is one of the targeted districts for vaccination. To assist medical staff in determining vaccination targets and assisting the public in obtaining information on the distribution of vaccinations in the Sukoharjo area, a system is needed that provides an overview of the mapping of vaccination recipients in the Sukoharjo area. In this study a website-based mapping system was designed using webGIS which can help provide an overview of vaccination recipients in the Sukoharjo area. The expected result of this design is a WebGis-based covid-19 vaccination distribution map that can assist vaccination officers in the district area in obtaining information on the distribution of Covid-19 vaccinations.